DIGITAL COUNSELLING APPS USING CHATBOT FOR STUDENTS WITH DEPRESSION - BYROSE KHAN, AINUL NAZRIYA (IRC, 2020)
Mental illness can cause a huge problem to the students and to their circle in the future if we do not acknowledge this issue. Therefore, the problem that have stated need to be solved. The reason why chatbot implemented in this project is because nowadays students feel shy to open up their problems directly to their family, friends even to the counsellor. By developing a digital counselling app for students with depression will be easy for students for ask question that they wanted to ask. This application is more private and secure and also whenever the students want to use it they easily can download it at their mobile phone. This application will help the students by giving them an accurate answer also with solution. Next, to carry out the user acceptance test with the counsellor and to the person who more knowledgeable in this term to ensure that the accessibility of the application is relevant and related to be used by the students with depression. Moreover, they are few things have been conducted to complete this project which is by collecting more information related to the project which is conduct a survey, do an interview session with the psychologist, also some observation and do some discussion with supervisor. The aim of this project is to help to control the number of students suffering from depression by providing them some solution by developing this mobile application may.